Evaluating the Performance of Certified Barley (Hordeum vulgare L.) Varieties under Rainfed and supplementary irrigation Conditions (Journal of Hama University, 2021)
The study was carried out at Abi Jerash Farm, Faculty of Agricultural Engineering, University of Damascus, during two consecutive agricultural seasons (2017-2018, 2018-2019), to evaluate the performance of seven locally certified barley varieties under rainfed, and supplementary irrigation conditions, in order to determine the most adaptive and grain yield productive varieties. The experiment was laid according to the complete randomized blocks design (RCBD), with the arrangement of split-split blots, with three replications. The average number of grains per square meter was significantly higher during the first growing season under supplementary irrigation conditions for the barley cultivar Fourat4 (27200 grains m-2), while it was significantly lower during the first growing season, under rainfed conditions in the barley cultivar Fourat7 (8334 grains m-2). The 1000-kenel weight, biological yield and grain yield were significantly higher during the first growing season under supplementary irrigation conditions in the barley variety Fourat5 (54.79 g, 131.1 and 5905 kg ha-1 respectively), while they were significantly lower during the first growing season under rainfed conditions in the two barley cultivars Araby Aswad and Fourat9 without significant differences between them (32.10, 33.62 g; 55.69, 58.49 g; 1183 and 1211 kg ha-1 respectively). The average of harvest index was significantly higher during the first growing season under supplementary irrigation conditions in the barley varieties Fourat4 and Fourat5 without significant differences between them (46.68 and 45.06% respectively). In general, the barley varieties Fourat5, Fourat4 and improved Araby Abiad are considered as the most adaptive cultivars to the targeted environmental conditions, because they were more adaptive to rainfed conditions and more responsive to supplementary irrigation, and could maintain significantly higher grain and biological yields compared with the other investigated varieties.